Rethinking IT in construction and engineering : organisational readiness (2019)
There have been significant advances in the development and application of information technology (IT), both in hardware and software. Such advances have clearly influenced the way in which organisations have integrated IT into their business environment. It is widely accepted that IT is becoming a key element of any organisational infrastructure. Indeed, many like to think that the level of an organisation’s reliance on IT in the twenty-first century is similar to the reliance on electricity in the previous century where it was not expected for an organisation to function without electricity. For example, networks, Internet, e-mail and office automation are seen as standard applications for “reasonable” size organisations. For small businesses, stand-alone applications such as e-mail, presentations and report writing are seen to be essential components for running any business. However, for larger organisations, the picture is more complex where IT infrastructure plays a key role in supporting core business functions. In this context, IT is being increasingly used to support business strategies as an enabler to leverage its potential to gain a competitive advantage and therefore new markets/clients. However, there is ample evidence that information systems (IS)/IT have failed to bring about a competitive advantage to organisations in spite of the large investments over the past decade. A large percentage of IS/IT systems have failed to achieve their intended business objectives. Previous studies in the area of “IS/IT failure” have shown that 80 to 90 per cent of IT investments did not meet their performance objectives. Such projects were abandoned, significantly redirected, or even worse, they were “kept alive” in spite of their failure. The cost of funding such projects and the missed opportunities of not benefiting from their intended capabilities constituted a tremendous loss for organisations. This dissolution in the strategic benefits of IS/IT is currently forcing many organisations not to invest in IT for any competitive advantage but for the reasons of bringing efficiency and effectiveness to business processes.